Pengaruh Intensitas Penggunaan Media Sosial dan Kecerdasan Emosional terhadap Prestasi Belajar Matematika Siswa SMP Walisongo - Muhimmatul Khoiroh; Yeva Kurniawati (De Fermat : Jurnal Pendidikan Matematika, 2026)
The purpose of this study is to analyze the influence of social media usage intensity and emotional intelligence on students’ mathematics achievement at Walisongo Junior High School. The social media platforms examined were TikTok and Instagram. This study employed survey and documentation methods as part of a quantitative approach. The population of this study consisted of all 51 students at Walisongo Junior High School. The social media usage intensity and emotional intelligence were measured using a questionnaire, while students’ mathematics achievement was measured based on odd semester final exam results. Data analysis was conducted using multiple linear regression analysis, but prior to this, normality and linearity tests were performed. The results of the data analysis yielded a Simultaneous Test (F-Test) with a significance level of 0.151 > 0.05, therefore, it can be concluded that H0 is accepted and H1 is rejected, meaning that there is no significant simultaneous influence of social media usage intensity (X1) and emotional intelligence (X2) on students’ mathematics achievement (Y) at Walisongo Junior High School. Thus, this study concludes that the variables of social media usage intensity and emotional intelligence do not have a significant influence, either partially or simultaneously, on students’ mathematics achievement